2004
DOI: 10.1051/forest:2004029
|View full text |Cite
|
Sign up to set email alerts
|

Climate-tree-growth relationships ofQuercus petraeaMill. stand in the Forest of Bercé (“Futaie des Clos”, Sarthe, France)

Abstract: -The past history of a 300-year-old Quercus petraea stand (the "Futaie des Clos", 8 ha) located 20 km from the town of Le Mans in the Forest of Bercé in the western part of France (Sarthe) was analysed by a dendroecological approach. According to the number of healthy trees alive (> 400), the stand age (> 300 years), and the dimensions of the trees (dia: 92 cm; height: 45.2 m), this plot constitutes one of the most remarkable oak grove in France. High competition pressure between trees appeared to be the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
74
3
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 38 publications
24
74
3
10
Order By: Relevance
“…4). Although the negative coefficients obtained for the winter-spring temperature tend to agree with the response of Q. petraea in western France (Lebourgeois et al, 2004) but the correlation does not reach p=0.05 level here, even if months were averaged. The weaker climatic signal in EW compared to LW or RW usually observed in oaks (Eckstein and Schmidt, 1974;Nola, 1996;Garcia-González and Eckstein, 2003) and a complete lack of significant response to temperature or precipitation for EW was reported also from a multisite study from Switzerland (Fonti and Garcia-González, 2008).…”
Section: Climatological Datamentioning
confidence: 55%
See 1 more Smart Citation
“…4). Although the negative coefficients obtained for the winter-spring temperature tend to agree with the response of Q. petraea in western France (Lebourgeois et al, 2004) but the correlation does not reach p=0.05 level here, even if months were averaged. The weaker climatic signal in EW compared to LW or RW usually observed in oaks (Eckstein and Schmidt, 1974;Nola, 1996;Garcia-González and Eckstein, 2003) and a complete lack of significant response to temperature or precipitation for EW was reported also from a multisite study from Switzerland (Fonti and Garcia-González, 2008).…”
Section: Climatological Datamentioning
confidence: 55%
“…Rbar runs generally below the 0.3 level for EW while exceed this level for LW and RW over the entire record (Fig. 2) Lebourgeois et al, 2004;Fonti and Garcia-González, 2008). Overall, dendrochronological statistics gave the impression that EW and LW carries different dendrochronological and probably different climatic signal as well.…”
Section: Stable Carbon Isotope Measurements and Subsequent Correctionsmentioning
confidence: 99%
“…Descriptive statistics indicated that the quality of site chronologies of A. glutinosa was comparable with the other chronologies of broad-leaf trees from the temperate zone of Europe (Dittmar et al, 2003;Lebourgeois, 2004;2005;Rozas, 2005). As these chronologies showed, MS (which expresses the relative variability in growth indices between adjacent rings) usually reaches 0.18-0.39.…”
Section: Growth Responses Of Alnus Glutinosa To Environmental Conditionsmentioning
confidence: 89%
“…AC, which indicates a dependence of current growth on the previous year's growth, normally ranges between 0.5-0.79 and thus corresponds with our results. Similarly, statistics reflecting the common growth variation in the individual ring-width series coincided with normal ranges: SNR 5.1-18, VFE 30-58%, MCAT 0.2-0.64, APC 0.77-0.92 (Dittmar et al, 2003;Lebourgeois, 2004;2005;Rozas, 2005). We can conclude that tree-ring width of A. glutinosa was sufficiently sensitive so as to reflect the signal of exogenous factors; our detected values for A. glutinosa were usually in the middle or higher range of the chronology statistics.…”
Section: Growth Responses Of Alnus Glutinosa To Environmental Conditionsmentioning
confidence: 99%
See 1 more Smart Citation